Oral Probiotics Alleviate Intestinal Dysbacteriosis for People Receiving Bowel Preparation - Deng, Xiaorong; Tian, Huakai; Yang, Rong; Han, Yiwen; Wei, Kehong; Zheng, Cihua; Liu, Zhaoxia; Chen, Tingtao (Frontiers in Medicine, 2020)
Background: Bowel preparation is necessary for successful colonoscopy, while it can seriously affect intestinal microbial composition and damage the intestinal mucosal barriers in humans. Methods: To figure out whether probiotics can sustain intestinal homeostasis and guard people’s health, the probiotic drug of Bifidobacterium Tetragenous viable Bacteria Tablets (P group, n=16) or placebo (C group, n=16) was used for volunteers receiving bowel preparation, and high-throughput sequencing method was applied to monitor their intestinal microbial changes. Results: The present results suggested that bowel preparation obviously reduced the intestinal microbial diversity, while taking probiotics significantly restored it to normal level. In addition, probiotics sharply reduced the abundance of pathogenic Proteobacteria, and obviously lowered the ratio of Firmicutes/Bacteroidetes compared with control group at phylum level (P < 0.05). And probiotics markedly decreased the abundance of pathogenic Acinetobacter and Streptococcus, while greatly enriched the relative abundance of probiotics Bacteroides, Roseburia, Faecalibacterium and Parabacteroides at genus level (P < 0.05). Conclusion: Probiotic drugs, e.g. Bifidobacterium Tetragenous viable Bacteria Tablets, can be used to restore intestinal dysbacteriosis caused by bowel preparation, and relieve side effects during colonoscopy.